Proposta metodológica para o estudo integrativo do risco de inundações: uma aplicação nos municípios de Taquara e Parobé, RS/Brasil - Knierin, Igor da Silva (2022)
The present thesis addresses, as a theme, the risk of flooding in the lower course of the Paranhana river basin in the municipalities of Taquara and Parobé, located in the Metropolitan Region of Porto Alegre. In the period between 1975 and 2020, 77 flood events occurred that caused damage and losses to subjects and their assets. During the development of the research, it became evident that there were difficulties in the availability of primary data, especially quantitative data that could subsidize the analysis of susceptibility, hazard, and risk of flooding. From this context, the objective of this research is to develop a methodological proposal for the integrative study of flood risk. The methodological procedures were based on an integrative and participatory approach for holistic risk analysis. The studies started with the inventory of flood event records for the period between 1975 and 2020, with the support of Municipal Civil Defense technicians and the local community, based on the indication of risk areas and non-structured interviews during the fieldworks. This subsidized the identification of the areas susceptible to flooding and, later, the validation of the research. For the analysis of the flood hazard and vulnerability areas, indicators and conditioning dimensions were selected. The analysis and attribution of weights for the respective variables were established based on the literature review, multicriteria decision with the Analytic Hierarchy Process and geographic information system support in the integration of quantitative and qualitative data and class definition. In a comprehensive and integrative manner, the joint analysis of hazard and vulnerability resulted in the identification of risk areas and the definition of low, medium, high, and very high degree classes. In the study area, the sites susceptible to flooding cover approximately 9.27 km² and extend over 28 census sectors in Taquara and 16 in Parobé, either partially or fully. In these areas, the fluvial dynamics are distinguished in processes of flooding of the Paranhana River, the Taquara stream and tributaries of the Paranhana River. Thus, the areas of hazard, vulnerability and risk were segmented into different sectors established according to the characteristics of the flooding processes, and the classes of high and very high hazard, low and high vulnerability, and high and very high risk were the most representative. The (re)production of space in the study area is marked by the installation of occupations near water courses and, in many cases, by subjects with high vulnerability. This represents a process of residential segregation. This problem portrays the lack of planning and socioeconomic inequality, often giving rise to an informal city. In view of this, the research can be used by the public administration to employ risk management practices. In areas of higher risk, the collaboration of multiple sectors of society is elementary for risk management to act in the prevention, mitigation, preparedness, response, and recovery to disasters.